Serosurvey of anti-treponema pallidum (syphilis), antihepatitis C virus and anti-HIV antibodies in homeless persons of São Paulo city, southeastern Brazil - Felipetto,Laís Giuliani (2021)
ABSTRACT Homeless persons have been considered as one of the most susceptible populations to sexually transmitted infections. In Brazil, these population experienced an increase of 140% from 2012 to 2020. Accordingly, the present study aimed to assess the seroprevalence of anti-Treponema pallidum, anti-HCV, anti-HIV antibodies, and the risk factors associated with homeless persons in a daytime attendance shelter of São Paulo city during the syphilis epidemic in Brazil. Blood samples of 116 volunteers and epidemiological data were conveniently collected in the shelter from June through August 2018. Detection of syphilis, HCV, and HIV antibodies was performed by chemiluminescent microparticle immunoassay (CMIA). CMIA-reagent samples for anti-T. pallidum antibodies were confirmed by Venereal Disease Research Laboratory (VDRL) non-treponemal test. VDRL non-reagent samples were confirmed by treponemal rapid immunochromatographic test. A rapid immunoblot assay confirmed seropositivity to HIV. Overall, anti-T. pallidum antibodies were observed in 29/116 (25.0%), anti-HCV antibodies in 4/116 (3.4%), and anti-HIV antibodies in 2/116 (1.7%) individuals, both co-infected with anti-T. pallidum antibodies. Associated risk factors for syphilis in homeless persons were being born or previously living in another city (p = 0.043) and becoming homeless due to family conflicts (p = 0.035). Besides homeless vulnerability, worldwide shortage of benzathine penicillin supply and increasing of syphilis testing access through rapid testing in primary health care services may have also impacted disease spreading at the time. The prevalence of syphilis found herein is the highest worldwide to date in this population.